Assessment of Indoor Levels of Carbon Monoxide Emission from Smoldering Mosquito Coils Used in Nigeria. (April 2022) - Elehinafe, Francis Boluwaji; Okedere, Oyetunji Babatunde; Adesanmi, Adewole Johnson; Jimoh, Eniola Mistura
Mosquito coils are commonly burnt in indoor environments to drive away mosquitoes which are vectors for malaria parasites. The levels of carbon monoxide (CO) emitted and human health implications during smoldering of 5 different brands of mosquito coils commonly used in Nigeria were investigated in 4 microenvironments of different sizes. The experiments were done by taking a scenario of a sleeping arrangement and the farthest distance between the coil burning and an arbitrary bed position in 4 different bedrooms of different sizes in poor ventilation condition of closed doors and windows. With monitoring device, ALTAIR 5X portable gas analyzer, at the position of the bed, measurements were taking at 2 minutes interval from start to the end of burning of each coil. The emission profile was determined by making concentration-time plots of CO emission to determine its levels from the burning of each brand of the mosquito coils in each microenvironment. From the emission profile, coils A, C, and D showed that CO levels exceeded Nigeria's Federal Ministry of Environment (FMEnv) and the World Health Organization (WHO) statutory limit of 9.0 ppm for indoor environments in each of the microenvironments between 3 and 7 hours after the burning commenced. It was concluded that the CO concentrations from smoldering mosquito coils is a function of the size of the microenvironment in which it is used. It was recommended that the size of a microenvironment be determined for consumption of a mosquito coil before it is released into the market.